Communication and Strategic Leadership: Its Role In Strengthening Hospital Governance - Gani, Nur Asni; Harun, Siti Hafnidar (Technium Social Sciences Journal, 2024)
The government nationally implements health programs. This is a challenge for hospitals as implementers of advanced health services after first level health facilities. The various changes that occur in the world of health in Indonesia in implementing programs require communication, strategic leadership, and hospital governance. This research uses a qualitative methodology with phenomenological analysis. Researchers conducted interviews with twelve informants from three hospitals. The results of research on strategic leadership are visionary leadership with sub-themes, namely: (1) Challenges are opportunities; (2) Studying applicable regulations and creating superior products; (3) Risk mitigation by mapping problems and solutions. These sub-themes describe the strategies carried out by leaders in implementing superior programs for the hospitals they lead.